Endorsement @fadhiljaidi Promotional Media in the Era of Disruption - Melyana, Azahra Aqita; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This research aims to analyse the influence of promotion on social media, especially TikTok, using the concept of endorsement by assessing aspects of trustworthiness, recognition, expertise, and attractiveness. The research method used is descriptive qualitative. The research was conducted with a focus on the TikTok account @fadiljaidi as a case study, which successfully attracted the attention of consumers and fans with a unique marketing approach. The research findings show that the unique marketing style of the @fadiljaidi account is able to capture the attention of its audience, despite not following common promotional strategies. The account managed to create authentic interest among TikTok users and Fadil Jaidi fans. The TikTok account @fadiljaidi is able to maintain its existence as an endorser and prove that his account is worthy of working with in achieving the marketing objectives of the product and/or service concerned. This is because he is able to show that he is an endorser who is confident, recognisable, has expertise, and attractiveness.